THE PROBLEM OF INFORMATION SPEED AND QUALITY IN INTERNET JOURNALISM (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The rapid rise of Internet journalism has revolutionized the media industry by enabling instant news delivery. However, this increased speed often compromises the accuracy, depth, and ethical standards of reporting. This article explores the growing tension between speed and quality in online journalism, analyzing how the digital race for attention affects news credibility, journalistic integrity, and public trust. Through recent developments and challenges, the paper emphasizes the need for responsible reporting practices in the age of digital immediacy.